Hypoxia‐Inducible Factor‐2α Signaling in the Skeletal System. (26th February 2023) - Mendoza, Sarah V; Genetos, Damian C; Yellowley, Clare E
ABSTRACT: Hypoxia‐inducible factors (HIFs) are oxygen‐dependent heterodimeric transcription factors that mediate molecular responses to reductions in cellular oxygen (hypoxia). HIF signaling involves stable HIF‐β subunits and labile, oxygen‐sensitive HIF‐α subunits. Under hypoxic conditions, the HIF‐α subunit is stabilized, complexes with nucleus‐confined HIF‐β subunit, and transcriptionally regulates hypoxia‐adaptive genes. Transcriptional responses to hypoxia include altered energy metabolism, angiogenesis, erythropoiesis, and cell fate. Three isoforms of HIF‐α—HIF‐1α, HIF‐2α, and HIF‐3α—are found in diverse cell types. HIF‐1α and HIF‐2α serve as transcriptional activators, whereas HIF‐3α restricts HIF‐1α and HIF‐2α. The structure and isoform‐specific functions of HIF‐1α in mediating molecular responses to hypoxia are well established across a wide range of cell and tissue types. The contributions of HIF‐2α to hypoxic adaptation are often unconsidered if not outrightly attributed to HIF‐1α. This review establishes what is currently known about the diverse roles of HIF‐2α in mediating the hypoxic response in skeletal tissues, with specific focus on development and maintenance of skeletal fitness. © 2023 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research.